Analisis Optimasi Performa Perangkat Android dengan Modifikasi Custom ROM - Basthanda, Fahrevi Dwiputra; Solehudin, Arip; Purwantoro, Purwantoro (Peneliti.net, 2024)
As the development of the Android operating system continues, the devices that use it also continue to evolve. For example, we can take a look at Xiaomi. Xiaomi uses MIUI as the user interface on its smart devices. Despite the release of the latest version, most of the recent versions have bugs or errors in the system that hinder the optimal performance of Android devices. To prove the performance differences, benchmarking is done using benchmarking applications. Benchmarking applications provide a performance score for Android devices. A higher benchmark score indicates higher Android device performance. To achieve optimal performance, custom ROM modifications are needed to maximize device performance. Custom ROM modifications can be done by altering the existing system with the help of the Magisk application. With the Magisk application, users can add modules, provided they have obtained root access. The overall test scores on GeekBench showed an improvement of 3.39%, and the total test scores on GeekBench experienced an increase of 3.64%. Launcher bugs, Dolby sound processing, microphone issues, and haptic feedback problems that occur in the stock ROM are eliminated in the custom ROM modification. However, a new bug arises in the form of storage space being read as 512 GB in the settings menu, which is different from the specifications of the Android device used, which is 256 GB. Another bug is the inability to hide the